Towards a more capacious, kindly,and caring criticality: A post-critical manifesto for ethical-relational-creative reviewing - Taylor, Carol A. Taylor; Hewlett, Sally; Hogarth, Hannah (Critical Studies in Teaching and Learning, 2023)
The words ‘criticality’, ‘critical’,and ‘critique’can often summon up painful, exposing,and difficult experiences. In a higher education system shaped by hierarchical cultures, abuses of power, performative metrics andcompetitiveness, many of us are often positioned as (and internalise a sense of ourselves as) lacking. This imputed sense of ‘lack’ begins early in our educational careersand its affective impress often stays with us. As PhD students, we are required to subject ourselves to critique in order topass confirmation processes; as article authors, our work stands or falls at the critical hands of journal reviewers and editors who, as gatekeepers, decide which of us is ‘accepted’ or ‘rejected’.We write as four members of the larger Get Up and Move!Collective, using the special issue call from CriSTaL to explore criticality, critical, critique, to revisit our own contested entanglements in/with criticality in higher education. We deploy the methodological approaches of compositing and composting to ponder the inimical conditions, negative behaviours,and ill-judged peer review comments that give rise to damaging modes of critique. From our work in the Collective, we consider what a more capacious, kindly,and caring criticality might look, feel,and be like. The article ends with APost-Critical Manifesto for Ethical-Relational-Creative Reviewing, which outlines a praxis for doing criticality differently.